Case report: Penile necrosis associated to paraphimosis with calciphylaxis due to terminal chronic kidney disease [version 1; peer review: 2 approved] - Grandez-Urbina, J.A. (2019)
Penile necrosis is a rare condition that may present in patients with diabetes mellitus or chronic kidney disease (CKD). The recommended treatment is controversial. We report a case of penile necrosis in a diabetic patient caused by episode of paraphimosis associated with uremic arteriopathy treated with partial amputation. Clinical Case: A 53-year-old male with a background of arterial hypertension, diabetes mellitus and CKD in hemodialysis. The patient presented with paraphimosis and glans necrosis. An emergency circumcision was carried out. A doppler ultrasound found fluid collection in the left corpus cavernosum, parietal vascular calcifications and vascular insufficiency in the corpus cavernosum that suggested necrosis. A partial amputation of the penis was carried out. After three years of follow-up, the outcome has remained favorable.